Estudio de factibilidad para crear la empresa K&O S.A.S, dedicada al turismo ecológico y aventura para personas solteras y solteros en la ciudad de Pereira Risaralda (2015)
This project sought to determine the feasibility of placing in operation a legally constituted company of tourism to promote various tour packages focused primarily to a niche of population of single men and single women in the city of Pereira. So a sample from the population objective (persons between 20 and 45 years, of both sexes) was selected, the survey was used as instrument of data collection which was processed through tables, graphs and analysis that allowed to establish people as tourism trends refers. The market study, which showed the feasibility of the project as a result from this variable, then is study the technical, administrative, legal and environmental, which also left to see the viability of business from this perspective was developed in this way. Finally addresses the financial study and financial evaluation of investment, throwing an IRR of the 24,37%, which is above the guy it was valued at 13.35%, the net present value also showed a positive result of $20.048.836, which indicates the feasibility of the project and under these perspectives is recommended its implementation. For the study was taken as a basis two authors recognized in the field of administration and economy; the first refers to the Lord Henry Fayol, which reflected the administrative theory which States that this can be applied to any human organization, and the second was the theory of Mr Michael Porter which establishes the competitive advantage of an organization in the business environment.